ความสัมพันธ์ระหว่างองค์ประกอบของคาร์บอน และความเข้มข้นของฝุ่นละอองกับลักษณะของชั้นบรรยากาศในเขตเมือง - สุวพร มณฑาสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The study in relation between particulate concentrations and atmospheric condition by adopting the high-volume air sampler sampling total suspended particulate (TSP) and particulate matter less than 10 micron (PM10) in 3 urban areas including Songkhla (Amphur Hat Yai, at the height level of 30, 60 and 125 meter), Bangkok (Rajdhevi District, at the height level of 38, 158 and 328 meter) and Chiangmai (Amphur Muang, at the height level of 12, 52 and 152 meter) along with using radiosonde to measure meteorological conditions above for 3 days continuously. And to find the chemical composition in PM10 by analyzing the organic substance that using ion chromatography and analyzing carbon composition that using thermal/optical carbon analyzer according to IMPROVE protocol. Study result revealed Bangkok and Chiangmai having the concentration of TSP and PM10 varied reversely to the height and the ratio of PM10/TSP varied reversely to the height level as well. In contrary to Amphur Hat Yai, the physical factors caused the turbulence that diluted the concentration of pollutant in middle height. The consideration of PM10/TSP ratio and meteorological condition revealed that there was insignificant relation, the potential factor could be caused by direct sources. The study result in percentage of PM10 composition in Bangkok including OC, EC, Na, NH4+, K+, Ca2+, Cl-, NO3-, SO42- and others species, found other species compositions might generated by heavy metal that was the highest figure at all height levels, the inferior including OC , SO42-, EC and NO3-. The predominant had the concentrations at medium level (158 meter) and upper level (328 meter) in equivalent figures significantly that could be able to indicate those sources including the emission from motor vehicles combustion. The study results of carbon composition in PM10 in Bangkok including OC1, OC2, OC3, OC4, EC1, EC2 and EC3, found that OC3, EC1 and OC2 concentrations were predominant. This indicated that carbon sources of the studied 3-height levels were released from engine exhaust (gasoline, liquid petroleum gas and diesel). Concentration of OC and EC varied directly to PM10 at all height levels that caused higher concentration of OC and EC at night time following PM10. The ratio of OC/EC varied reversely to the height and related significantly to relative humidity, temperature and mixing height.